REMOVAL OF CADMIUM, COPPER, LEAD AND ZINC FROM SIMULATED INDUSTRIAL EFFLUENTS USING SILICA POWDER - Javed, T.; Awan, F. A.; Arshad, M.; Mashiatullah, A.; Iftikhar, F. J.; Khan, S. N. (The Nucleus, 2013)
Rapid industrial development have led to the recognition and increasing understanding of interrelationship between pollution, public health and environment. Industrial development results in the generation of industrial effluents, and if untreated results in water, sediment and soil pollution. In Pakistan most of the industrial effluents are discharged into surrounding ecosystems without any treatment. Industrial wastes and emission contain toxic and hazardous substances, most of which are detrimental to human health. Extensive efforts are being made around the world for the removal of heavy metal from industrial effluents. A laboratory scale study was designed for removal of Cd, Cu, Pb and Zn from simulated solutions at various weight of silica (0.5gm, 1 g, 2 gm, 3gm and 4 gm), Voltammeter was used to quantify the metals. Maximum removal of all metals was achieved with 4 gm of silica. Absorption of lead onto silica was higher than other metals.